A gain‐tuning method for almost disturbance decoupling problems of nonlinear systems with zero dynamics. (7th February 2022) - Liu, Xiaoping; Wang, Zhengqi; Wang, Wilson
Abstract: In this paper, a gain‐tuning method for almost disturbance decoupling problems of nonlinear systems with zero dynamics is developed. Firstly, a linear subsystem is formed by linearizing the nonlinear system. Then, a linear matrix inequality can be formed for the linear subsystem. After that, a linear state‐feedback controller can be obtained by solving the linear matrix inequality. A nonlinear state‐feedback controller can be obtained for the original nonlinear system by using backstepping design method. Another linear state‐feedback controller can be derived by linearizing the nonlinear state‐feedback controller. Finally, the backstepping gains can be solved by equating the two linear controllers. The detailed derivations of the method are provided. Some comparisons with the existing techniques are discussed. Moreover, the designed method is verified by simulations and some comparisons are made accordingly.